Performance Analysis for the Magnetically Coupled Resonant Wireless Energy Transmission System - Jinguo Liu; Xuebin Zhang; Jiahui Yu; Zhenyao Xu; Zhaojie Ju (Complexity)
As a new wireless energy transmission technology, magnetically coupled resonant wireless energy transmission system (MCRETS) is not easily affected by obstacles in the transmission process, and the transmission distance is relatively far. However, how to balance the relationship between transmission efficiency and power to achieve optimal performance is still a huge challenge. In addition, few studies have theoretically investigated the factors affecting the wireless energy transmission system to obtain an optimal solution. Here, through unprecedented theoretical analysis, we find the exact parameters of system optimization and verify them by simulation and experiments. First, the optimal topology of MCRETS is obtained through theoretical analysis and comparison of topologies. Second, to improve the transmission performance of MCRETS, its impact factors, including transmission distance, resonant frequency, relay coil, and relative position of launch and receiving coils, are analyzed in detail to get accurate parameters. Furthermore, based on the analysis, we propose an unprecedented concept for balancing optimal efficiency and power, which is named the power product. Finally, the effectiveness of the proposed method is verified through analysis and experimental results. These findings shed light on the relationship between efficiency and power and provide a comprehensive theoretical basis for subsequent research.